Respuesta :

Answer:

Step-by-step explanation:

nth term = a +(n-1)d

a3 = 116 ;   a + 2d = 116 ---------(i)

a7 = 180;   a + 6d = 180 -------(ii)

multiply (ii) by -1. so a will be eliminated

           a + 2d = 116 ---------(i)

(ii)*-1    -a - 6d = -180 -------(ii)   { Now add the two equations}

              - 4d = -64

                   d = -64/-4

                  d = 16

Plug in the value of d in equation (i),

a + 2*16 = 116

a + 32 = 116

        a = 116 - 32

        a = 84

12th term = 84 + 11* 16 = 84 + 176 = 260

ACCESS MORE